Paradoxes Of Higher Education Reforms: Implications On The Malaysian Middle Class - Aihara, Akihito (Penerbit Universiti Sains Malaysia (USM Press), 2009)
What is the middle class? This conceptual conundrum remains unsolved, yet higher education in Malaysia is deemed as one of the constituents. With special reference to higher education reforms in the 1990s, this paper agrees with the literature arguing that the Malaysian middle class is heterogeneous. Empirical evidence from Population and Housing Census Malaysia 2000 indicates the diversities and complexities within higher education that flow over to the terrain of the Malaysian middle class. Meanwhile, this paper leaves open an old but fundamental question: what is the notion of a class underlying the Malaysian middle class studies that accept its heterogeneity but use the term, "the middle class" or "the middle classes"?